Reform and Practice of Differentiated Teaching in Compiler Technology Courses Driven by Task Engines - Huang, JianCai; Yue, Yan (International Journal of Computer Science and Information Technology, 2026)
To address issues such as the abstraction of knowledge points in compiler technology courses, significant differences in students' foundations, the disconnect between theory and practice, and insufficient integration of ideological and political education, a differentiated teaching model based on a task engine is proposed. By breaking down the core course knowledge points into stepwise tasks, a system for generating personalized learning paths is constructed, organically integrating real-life scenarios and ideological and political elements into task design, thereby achieving the dual objectives of "teaching according to students' abilities" and "value guidance." Teaching practice shows that this model can effectively enhance students' learning interest, practical ability, and ideological and political literacy, significantly improving teaching effectiveness.